2019
DOI: 10.1126/scirobotics.aax7112
|View full text |Cite
|
Sign up to set email alerts
|

Soft phototactic swimmer based on self-sustained hydrogel oscillator

Abstract: Oscillations are widely found in living organisms to generate propulsion-based locomotion often driven by constant ambient conditions, such as phototactic movements. Such environment-powered and environment-directed locomotions may advance fully autonomous remotely steered robots. However, most man-made oscillations require nonconstant energy input and cannot perform environment-dictated movement. Here, we report a self-sustained soft oscillator that exhibits perpetual and untethered locomotion as a phototacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
262
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(285 citation statements)
references
References 41 publications
2
262
0
Order By: Relevance
“…It typically occurs in certain living organisms, such as insects, jellyfish, or zooplankton, that are considered to be related to navigation or photosynthesis 65,66. Very recently, Zhao et al reported a swimmer robot based on a photosensitive hydrogel oscillator showing negative phototactic movement (away from the light source) in water driven by a laser 4. They further developed an artificial phototropic system based on hydrogels or a series of photoresponsive polymers that can autonomously aim and align in the incident light direction in three dimensions 67.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It typically occurs in certain living organisms, such as insects, jellyfish, or zooplankton, that are considered to be related to navigation or photosynthesis 65,66. Very recently, Zhao et al reported a swimmer robot based on a photosensitive hydrogel oscillator showing negative phototactic movement (away from the light source) in water driven by a laser 4. They further developed an artificial phototropic system based on hydrogels or a series of photoresponsive polymers that can autonomously aim and align in the incident light direction in three dimensions 67.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include the involuntary beating of the heart muscle, neuron impulses, cell cycling, water waves, etc., which can be regarded as a type of persistent motor that continuously outputs mechanical work. The unique characteristics of oscillation as well as its potential for various applications (e.g., soft robots for walking or swimming, self‐cleaning surfaces, and energy coupling) inspire us to devise novel types of artificial self‐oscillating actuators with self‐sustained autonomous motion under a constant environment 3–8. However, at present, most of the smart actuators for converting external environmental stimuli into mechanical deformation can only produce unsustainable single motion under constant stimulation, which lacks the autonomy compared with self‐oscillation in nature 9–19.…”
Section: Introductionmentioning
confidence: 99%
“…[30,70,74] Recently, He's group reported an Au NPs-embedded PNIPAm (AuNPs/PNIPAm) hydrogel pillar, and it can oscillate under constant light owing to a builtin feedback loop ( Figure 2C). [75] The oscillating displacement was about 0.3 mm corresponding to an oscillation temperature from ≈30 to 34 °C ( Figure 2D). They also adopted other photothermal agents (GO, polyaniline) and poly(2-(diethylamino) ethyl methacrylate) hydrogel to achieve the full-automatic phototaxis movements.…”
Section: Molecular Sorption/desorptionmentioning
confidence: 98%
“…Reproduced with permission. [75] D) the oscillation displacement and temperature as a function of time for the AuNP/PNIPAm hydrogel. Reproduced with permission.…”
Section: Phase Transitionmentioning
confidence: 99%
“…Morphing materials have promising applications in biomedical devices, flexible electronics, soft robotics, and so forth. [ 1–5 ] Many efforts have been made to realize controllable deformations of intelligent materials including liquid crystalline elastomers and shape‐memory polymers. [ 6,7 ] Among these materials, hydrogels have received increasing attention owing to their similarity to soft bio‐tissues and multiresponsiveness to external stimuli.…”
Section: Figurementioning
confidence: 99%